Application of microbial organic fertilizers promotes the utilization of nutrients and restoration of microbial community structure and function in rhizosphere soils after dazomet fumigation - Huang, Bin; Chen, Yuxuan; Pei, Zhouyang; Jiang, Lianqiang; Zhang, Yu; Wang, Jing; Wang, Jie (Frontiers in Microbiology, 2023)
Soil fumigant dazomet is a broad-spectrum nematicide and fungicide that can kill non-target microbes. Fungicides or organic fertilizers are often added after fumigation to improve the recovery of soil microbes. However, the effect of adding microbial organic fertilizers (MOF) after fumigation on the structure and function of rhizosphere soil microbial communities of crops is unclear. Therefore, we investigated the effects of adding Junweinong and Junlisu MOFs after dazomet fumigation on the structure and function of rhizosphere microbial communities and its relationship with soil properties and enzyme activities. The results showed that the addition of these two MOFs after dazomet fumigation significantly reduced the rhizosphere soil available phosphorus, available potassium, organic matter content, and urease, alkaline phosphatase, and catalase activities, but increased the soil pH compared with the fumigation treatment. The application of MOFs after fumigation resulted in significant enrichment of bacteria such as Gaiella, norank_f_Vicinamibacteraceae, and Flavisolibacter and fungi such as Peroneutypa, Olpidium, and Microascus in the rhizosphere soil of the crop and increased the relative abundance of functional genes of 13 kinds of amino acids metabolism, pyruvate metabolism, TCA cycle, and pentose phosphate pathway as well as endophytic and epiphytic functional groups in the rhizosphere soil. In particular, NH4+-N, pH, and AK had the greatest effect on rhizosphere microorganisms. Overall, the addition of MOFs after fumigation promoted crop root nutrient uptake, enhanced rhizosphere soil microbial metabolism, allowed more beneficial communities to colonize the roots, and promoted soil microbiological health.